Paediatric interventional cardiology in Costa Rica: diagnostic reference levels and estimation of population dose. (25th January 2018) - Ubeda, C; Vano, E; Salazar, L; Retana,; Santos, F; Gutierrez, R; Manterola, C
Abstract: The goal of the present study was to propose a set of national diagnostic reference levels (DRLs) in Costa Rica for paediatric interventional cardiology (IC) procedures classified by age and weight and to estimate the collective dose of the paediatric population from these intervention practices. The data collection period was May 2016 to May 2017. The third quartile of patient dose data distributions for kerma–area product (KAP) values was set as the national DRLs. A sample of 154 paediatric IC procedures (collected in the national paediatric hospital with a single x-ray system) was used and divided into four age ranges and five weight ranges. The national DRLs obtained for KAPs by age range were 1.79 Gy cm 2 (<1 year) to 23.0 Gy cm 2 (10–15 years). The national DRLs obtained for KAPs by weight range were 1.0 Gy cm 2 (<10 kg) to 49.6 Gy cm 2 (50–79 kg). The contribution to the collective dose of the population of Costa Rica amounted to 0.78 person Sv.